Determinasi Pengelolaan Keuangan Mahasiswa Penerima Kartu Indonesia Pintar (KIP) - Riza Ul Fahmi; Sri Sinta; Ansari Rizal; Wiki Noviandi (Jurnal Studi Manajemen Bisnis, 2026)
This study examines the influence of lifestyle, financial literacy, and financial attitude on financial management among students receiving the Indonesia Smart Card scholarship in the Management Economics Study Program at Abulyatama University. The study is motivated by the need for effective financial management amid limited financial resources and increasing lifestyle pressures. Using a quantitative survey, data were collected from 69 students in a population of 227. Multiple linear regression analysis was employed to test the hypotheses. The results show that lifestyle and financial attitudes have a significant positive effect on financial management, whereas financial literacy does not. These findings suggest that financial behavior and attitudes play a more dominant role than financial knowledge in shaping students’ financial management. This study contributes to the literature on personal financial management, particularly among scholarship recipients, and highlights the importance of fostering positive financial attitudes and managing lifestyle patterns to improve financial outcomes.